The Influence of Campus Environment and Human Resource Management on Productivity in Economics Faculty Students at Medan State University - Putri, Nada Deliza; Khairunnisa, Khairunnisa; Sianturi , Reni Marlina; Hutauruk, Naomi; Fahyed, Fadhil Al; Siregar, Zulkarnain (Holistic Science, 2024)
The study aims to analyze the impact of campus environment and human resource management on productivity in economics faculty students at Medan State University. This research applies quantitative methods to study the relationship between the various variables. The free variables in this study are student productivity with its bound variables namely campus environment and human resource management. The data in this study is primary data by spreading the questionnaire as a data collection method. Respondents to this study were 80 students at the Faculty of Economics of State University of Medan. The hypothesis was tested with the help of SmartPLS software. Based on the test the researchers found that the campus environment and human resource management had a positive and significant influence on student productivity.